The levels of nitric oxide and metabolites in Behcet's disease - Kokcam, Ibrahim; Dertlioglu, Selma Bakar (Tubitak Scientific & Technological Research Council Turkey, 2011)
Aim: Endothelial damage and dysfunction are held responsible for the etiopathogenesis of Behcet's disease (BD). In the present study, we aimed to investigate the relationship of BD with nitric oxide (NO), asymmetrical dimethylarginine (ADMA), symmetrical dimethylarginine (SDMA) and L-arginine levels, which are known to play a role in the pathogenesis of vasculitis. Materials and methods: Sixty patients enrolled in the study were allocated to groups as follows: active/inactive patient groups; the patient group with active/inactive vessel involvement, and mucocutaneous patient group without vessel involvement. Results: NO, SDMA, ADMA levels of the active patients and SDMA and ADMA levels of the inactive patients were found to be significantly higher than those of the healthy controls. SMDA and ADMA levels in the group with active vessel involvement; NO, SDMA, ADMA, and L-arginine levels in the group with inactive vessel involvement; and, NO, SDMA, and ADMA levels of the mucocutaneous group were significantly higher than those of the healthy controls. However we detected no statistically significant difference among the patient groups. Conclusion: These criteria cannot be utilized in evaluating the activity of the disease and in predicting vessel involvement.
Behçet hastalarında nitrik oksit ve metabolitlerinin düzeylerinin araştırılması
Keywords: Behcet's disease; nitric oxide; asymmetrical dimethylarginine; symmetrical dimethylarginine; L-arginine